Calificación de instalación, operación y desempeño del equipo autoclave de desechos Yamato SK110C en laboratorio ALKOFARMA E.I.R.L. - Alva Cuba, Roel Jamis (2017)
The objective of the present work was to describe the installation, operation and performance of the Yamato SK110C autoclave waste equipment in the laboratory ALKOFARMA E.I.R.L, for which it was developed under the descriptive, observational and experimental methodology. The work was divided into three stages, installation qualification, operating qualification and performance rating. The results obtained in the installation qualification are in accordance with the criteria demanded by the manufacturer, the parameters evaluated in the stage of operation are within the acceptance range and the performance qualification complies in all evaluated points, achieving the sterilization. It is concluded that the qualification of installation, operation and performance developed in the Yamato SK110C waste autoclave in the laboratory ALKOFARMA E.I.R.L. are compliant with the established acceptance criteria